2021
DOI: 10.21203/rs.3.rs-183793/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupling Fuzzy logic and Analytical Hierarchy Process (FAHP) with GIS for Landslide Susceptibility Mapping (LSM) in Ziz upper watershed, SE Morocco

Abstract: Landslides have become a destructive geo-hazard in many countries, which seriously cause damage to the human lives, infrastructure and properties. They result from the movement of soil on unstable slopes in mountainous areas. This caught attention to study the increasing incidences of landslides in many areas including Morocco. In this study, the fuzzy logic and analytical hierarchy process (FAHP) integrated with the geographic information system (GIS) are used to determinate the landslide susceptibility model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Whereas, the regions with values closer to 0 are considered less susceptible. -i, it is shown that all parameters are closer to the value 1 in the upstream western parts of the study area (Manaouch et al, 2021).…”
Section: Fuzzy Methodsmentioning
confidence: 76%
See 3 more Smart Citations
“…Whereas, the regions with values closer to 0 are considered less susceptible. -i, it is shown that all parameters are closer to the value 1 in the upstream western parts of the study area (Manaouch et al, 2021).…”
Section: Fuzzy Methodsmentioning
confidence: 76%
“…After assigning weights to the parameters according to the AHP method, the parameter maps are converted to fuzzy maps and using the Raster spatial analysis tool in ArcGIS 10.5 a landslide susceptibility map is produced. According to the resulting map (Figure 4), it is found that the vulnerability is very high in the upper western and northern parts of the study area (Manaouch et al, 2021). These areas are dominated by mountain pastures.…”
Section: Fahp Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Researchers have used quantitative approaches in contemporary periods, viz. artificial neural networks (Lucchese et al 2021;Jacinth Jennifer and Saravanan 2021), logistic regression analysis (Gu et al 2021;Crawford et al 2021;Sujatha and Sridhar 2021), fuzzy logic (Bahrami et al 2021;Manaouch et al 2021;Nanehkaran et al 2021), multivariate regression analysis (Arabameri et al 2019;Chu et al 2019;Pham et al 2021), bivariate regression analysis (Zhou et al 2021) to delineate LSZ. Machine learning approaches are now widely used to predict natural disasters such as floods, wildfires, earthquakes, and doughtiness, among others (Hong et al 2018;Ahmadlou et al 2019).…”
Section: Introductionmentioning
confidence: 99%